Examining the impact of farm management practices on wheat production: Does agricultural investment matter? - Abbas Ali Chandio; Mohamad Alnafissa; Waqar Akram; Muhammad Usman; Mumtaz Ali Joyo (Heliyon, 2023)
Over the years, the allocation of public funds toward agriculture has consistently played a pivotal role in facilitating the modernization and commercialization of the agricultural industry. Similarly, the integration of technological breakthroughs plays a pivotal role in guaranteeing the sustainability of food production, not solely for the present populace but also for subsequent generations. The present study examines the impact of public investment in agriculture and farm management practices, specifically focusing on cultivated area, fertilizer use, pesticide application, total agricultural machinery, and rural labour force on wheat production in nine provinces of China. The study encompasses the period from 1995 to 2020. This study employs advanced econometric techniques, such as second-generation unit root procedures (CADF and CIPS) and the Westerlund cointegration method, to investigate the stationarity properties and cointegration of the variables. The findings derived from the AMG and CCEMG methods indicate that public investment plays a statistically significant influence on wheat production. In the context of production-related variables, long-term wheat production is statistically and substantially influenced by the total area under cultivation, fertilizer use, and pesticide application. Besides these results, the Dumitrescu and Hurlin causality test reveals a unidirectional causality from agricultural machinery power consumption to wheat production. Furthermore, bidirectional causality exists between public investment, cultivated area, fertilizer use, labour, and wheat production. These results provide vital implications and valuable insights for policymakers in China, which may furnish novel policymaking options for sustainable food production through strategic investments in research and development, irrigation systems, and technological advancements.